The inclusion and access of social housing movements to Minha Casa Minha Vida: the emergence of the Entidades modality | Inserção e acesso dos movimentos sociais de moradia no Programa Minha Casa Minha Vida: o surgimento da modalidade Entidades - Jesus, Patricia Maria de (Revista Brasileira de Estudos Urbanos e Regionais, 2016)
In 2009, when the Minha Casa Minha Vida Program was introduced, there was a specific modality contained within its portfolio, which was to be executed by non-profit entities. However, because it was known from the very start that this program had been proposed and structured by those from within the civil construction industry, we decided to undertake an investigation, which could explain the emergence of a modality called Entidades, together with its scope. The present article analyzes and discusses the importance of the advent of this modality, seeking to problematize it from the viewpoint of the insertion and access of a specific group: the social housing movements. The analysis has been based on the literature, legislation and documentation regarding the program, as well as interviews with leaders and empirical research into projects under construction in the city of São Paulo and the metropolitan region.